Analisa Peluang Dan Ancaman Perdagangan Produk Kerajinan Dan Kebijakan Untuk Mengatasinya (Studi Kasus Indonesia dengan Singapura) - Aprilia Dwi Aisyah; Daspar Daspar (CV. ITTC INDONESIA, 2025)
Indonesian crafts and Singapore have great potential to strengthen cooperation between the two countries' economies. Indonesian handicrafts have an extensive cultural heritage and craftsmanship, offering a range of unique and high-quality products. As a dynamic global trading hub, Singapore offers a vast and diverse market for these handicrafts. Factors affecting the crafts trade between Indonesia and Singapore, trade policies, consumer preferences, effective marketing strategies, and more. Trader data and market trend analysis allow opportunities and challenges to be considered when developing trade in both countries. Close cooperation with the government, economic stakeholders, and other stakeholders is key to expanding Indonesian crafts in Singapore. Singapore's success in the competitive market also requires the development of innovative marketing strategies, improved product quality, and a high level of application.